Pengaruh Fasilitas Laboratorium Akuntansi, Pengantar Akuntansi, dan Computer Knowledge Terhadap Hasil Belajar Komputer Akuntansi Dengan Intensitas Belajar Sebagai Variabel Moderasi - Lailatur Rahmah; Rochmawati Rochmawati (FKIP, Universitas Banten Jaya, 2023)
This study aimed to analyze learning intensity can moderate the influence of accounting laboratory facilities, introductory understanding of accounting, and computer knowledge on learning outcomes of accounting computers for class XI AKL AKL SMKN 2 Buduran. This type of research is including quantitative research. The samples used were 108 students of class XI AKL SMKN 2 Buduran using saturated sampling. Data collection techniques using questionnaires, interviews, and documentation. The data analysis technique used Structural Equation Model Partial Least Square (SEM PLS) with SmartPLS 3.0 software. The results of the study show that: (1) There is a significant influence of accounting laboratory facilities on the learning outcomes of accounting computers. (2) There is a significant influence of the introductory understanding of accounting on the learning outcomes of accounting computers. (3) There is no significant influence of computer knowledge on the learning outcomes of accounting computers. (4) Learning intensity strengthens the influence of accounting laboratory facilities on the learning outcomes of accounting computers. (5) Learning intensity strengthens the influence of an introductory understanding of accounting on the learning outcomes of accounting computers. (6) Learning intensity weakens the influence of computer knowledge on the learning outcomes of accounting computers.